Correlation between HbA1c level and LDL cholesterol level in ischemic stroke patients - Gupta, Gaurav; Aquiqe, Mohammad; Giri, Richa; Verma, Shivendra (International Journal of Advances in Medicine, 2020)
Background: Defects in insulin action and hyperglycemia could lead to Dyslipidemia in patients with diabetes. Methods: Cross sectional study carried out in patients presenting with ischemic stroke to medicine emergency unit of the LLRH Hospital from January 2018 to October 2019.Patient of age group 40-80 years The subjects in the present study were 450 patient comprised of 235 cases with ischemic stroke of age group of 40-80 years and 215 health y controls of age group of 40-80 years. Results: The correlation between these two variable as elicited from data obtained from study and, is significant (p<0.0001). The sensitivity of this correlation in the context of ischemic stroke is 75%, while the specificity is 60%. However, an impressive negative predictive value of 91% suggests a beneficial effect of normal or well controlled diabetes and Dyslipidemia. Conversely, a modest positive predictive value of 29% does not appear to help in utilizing this correlation as a measure of future likelihood of ischemic stroke. p value 0.00005 inference-highly significant. Conclusions: Study show statistically significant association (p < 0.001) of increased levels of HbA1c and LDL-C in patients of ischemic stroke.